2007
DOI: 10.1103/physrevlett.99.137402
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Spectroscopy of Carbon Nanotube Bundles: Evidence for Exciton Energy Transfer

Abstract: Photoluminescence is commonly used to identify the electronic structure of individual nanotubes. But, nanotubes naturally occur in bundles. Thus, we investigate photoluminescence of nanotube bundles. We show that their complex spectra are simply explained by exciton energy transfer between adjacent tubes, whereby excitation of large gap tubes induces emission from smaller gap ones via Förster interaction between excitons. The consequent relaxation rate is faster than nonradiative recombination, leading to enha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
282
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(301 citation statements)
references
References 32 publications
13
282
3
3
Order By: Relevance
“…3,4 The changes noted in photoluminescence excitation (PLE) maps upon bundling was attributed to exciton transfer between species. An important limitation in those studies is the ambiguity inherent to ensemble measurements, where interpretation can be complicated by overlapping contributions from several SWNT species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The changes noted in photoluminescence excitation (PLE) maps upon bundling was attributed to exciton transfer between species. An important limitation in those studies is the ambiguity inherent to ensemble measurements, where interpretation can be complicated by overlapping contributions from several SWNT species.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a few studies have addressed the luminescence from SWNT bundles and revealed a signature of energy transfer to SWNTs with the lowest energy. [3][4][5][6] Förster resonance energy transfer (FRET) is an important research topic with direct applicability to biological systems 7 and potential impact for the design of light emitting or harvesting devices. 8 In FRET, 9 electronic excitations in a fluorescent donor (D) molecule transfer to an acceptor (A) molecule, which shows fluorescence at lower energy (see ref 10 for a general review).…”
Section: Introductionmentioning
confidence: 99%
“…CNT bundles show complex PLE spectrum involving EET between tubes. In [47] it is shown that radiationless relaxation enhances PLE of acceptor tubes. This can be beneficial as it surpasses the poor performance of individual CNTs.…”
Section: Photoluminescence Excitationmentioning
confidence: 99%
“…Spataru et al [46] reported a theoretical estimation of intrinsic exciton lifetime of about ~10 ps for lowest bright excitons in isolated SWNT. However, a recent photoluminescence study of small bundles in solution shows that exciton energy transfer between semiconducting SWNTs within bundles can be an efficient carrier relaxation channel [47]. The multicomponent carrier recombination dynamics inherent to nanotubes comes from (i) intraband thermalisation (with relaxation time of 200 fs) [48], (ii) exciton energy transfer between adjacent tubes in bundles [47], (iii) nonradiative recombination through dark excitonic states and excited carrier tunnelling on metallic tubes (m-CNTs) (500 fs-10 ps) and (iv) the radiative recombination through bright excitonic states (10-500 ps) [41,49].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Very recently, resonant exciton energy transfer between semiconducting nanotubes has been observed for SWNTs in micelles suspensions for the first time and was explained by near-field coupling corresponding to fluorescence resonance energy transfer (FRET) well-known for molecular systems. 11 In ref 12, spectroscopic signatures of internanotube transfer were observed, and it was suggested that efficient coupling results from carrier migration requiring direct physical contact. In ensemble measurements, however, the identification of donor and acceptor spectral signatures is complicated by overlapping contributions from different nanotube species, including phonon-assisted absorption and possible emission from lower lying defect-associated states.…”
mentioning
confidence: 99%